Senior education as a form of prevention from social exclusion - Krupková, Kateřina; Bělík, Václav; Nováková, Barbora (Edukacja Dorosłych, 2023)
The article emphasizes the importance of senior education being a form of prevention from social exclusion. The first part is dedicated to basic terminology and the opportunities in senior education within the Czech Republic are also being defined. Particular attention is devoted to the risks associated with the period of the Covid-19 pandemic when the risk of social exclusion increased due to the impossibility of interaction with others, so the seniors often became a neglected group in social isolation.